Profiling of the Peripheral Blood Mononuclear Cells Proteome by Shotgun Proteomics Identifies Alterations of Immune System Components, Proteolytic Balance, Autophagy, and Mitochondrial Metabolism in Glaucoma Subjects - Giammaria, Sara; Pandino, Irene; Zingale, Gabriele Antonio; Atzori, Maria Grazia; Cavaterra, Dario; Cecere, Michela; Michelessi, Manuele; Roberti, Gloria; Tanga, Lucia; Carnevale, Carmela; Vercellin, Alice Verticchio; Siesky, Brent; et al. (ACS omega, 2025)
Glaucoma is a chronic optic neuropathy and is the second cause of irreversible blindness worldwide. Although the pathogenesis of the disease is not fully understood, the death of retinal ganglion cells and degeneration of the optic nerve are likely promoted by a combination of local and systemic factors. Growing attention has been paid to nonintraocular pressure risk factors, including mechanisms of inflammation and neuroinflammation. Phenotypical and molecular alterations of circulating immune cells, in particular, lymphocyte subsets, have been documented in murine models of glaucoma and in human subjects. Very recently, oxygen consumption rate and nicotinamide adenine dinucleotide levels of human peripheral blood mononuclear cells (PBMC) have been proposed as biomarkers of disease progression, thus suggesting that immune cells of glaucoma subjects present severe molecular and metabolic alterations. In this framework, this pilot study aimed to be the first to characterize global proteome perturbations of PBMC of patients with primary open-angle glaucoma (POAG) compared to nonglaucomatous controls (control) by shotgun proteomics. The approach identified >4,500 proteins and a total of 435 differentially expressed proteins between POAG and control subjects. Clustering and rationalization of proteomic data sets and immunodetection of selected proteins by Western blotting highlighted significant alterations of immune system compartments (i.e., complement factors, regulators of immune functions, and lymphocyte activation) and pathways serving key roles for immune system such as proteolysis (i.e., matrix metalloproteinases and their inhibitors), autophagy (i.e., beclin-1 and LC3B), cell proliferation (Bcl2), mitochondrial (i.e., sirtuin), and energetic/redox metabolism (i.e., NADK). Based on these findings, this proteomic study suggests that circulating immune cells suffer from heterogeneous alterations of central pathways involved in cell metabolism and homeostasis. Larger, properly designed studies are required to confirm specifically how immune cellular alterations may be involved in the pathogenesis of both neuroinflammation and glaucomatous disease.